2021
DOI: 10.1136/jitc-2020-001638
|View full text |Cite
|
Sign up to set email alerts
|

CMTM6 and PD-L1 coexpression is associated with an active immune microenvironment and a favorable prognosis in colorectal cancer

Abstract: BackgroundCKLF-like MARVEL transmembrane domain-containing 6 (CMTM6), a programmed death-ligand 1 (PD-L1) regulator, is widely expressed in various tumors and regulates the immune microenvironment. However, its prognostic value remains controversial, and the roles of CMTM6 in colorectal cancer (CRC) are still unknown. In this study, we aimed to elaborate the expression patterns of CMTM6 and PD-L1 in CRC and investigate their relationship with the infiltration of T cells and the prognosis of patients with CRC.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 44 publications
4
41
0
Order By: Relevance
“…They also found that CMTM6 levels are positively correlated with the immune response in CRC cells [32]. Similarly, we found that the expression of PD-L1 in TC and IC were positively correlated with CMTM6 in CRC.…”
Section: Pd-l1supporting
confidence: 80%
“…They also found that CMTM6 levels are positively correlated with the immune response in CRC cells [32]. Similarly, we found that the expression of PD-L1 in TC and IC were positively correlated with CMTM6 in CRC.…”
Section: Pd-l1supporting
confidence: 80%
“…Conlon, liver, lung cancers are the common malignancies in most countries, and immune cells infiltration into tumour tissue and immune cells exhaustion lead to a poor prognosis [ 1 4 ]. The infiltration number and exhaustion state of immune cells could exert a key role in cancer progression, and immune combination therapy is becoming a promising strategy for enhancing traditional chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…The levels of CMTM6 mRNA and protein were both applied for the prognosis analysis of different types of tumor and contradictory conclusions were obtained. At the mRNA level, a high level of CMTM6 is correlated with better survival in gastric cancer, colorectal cancer [20,29], while high level of CMTM6 is correlated with worse survival in gliomas [16]. At the protein level evaluated by immunohistochemistry, highly expressed CMTM6 indicates poor prognosis in gastric cancer, HNSCC, hepatocellular carcinoma [21,[30][31][32].…”
Section: Discussionmentioning
confidence: 99%